The dark side of reciprocity - Natalia Montinari (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
Whether friendship or competitive relationships deserve to be encouraged in the workplace is not obvious a priori. In this paper we derive the conditions under which a profit-aximizing employer finds it convenient to induce a rat race among workers exhibiting horizontal reciprocity in order to obtain underpaid or unpaid extra effort. We characterize the optimal compensation scheme under both symmetric and asymmetric information about workers' actions, and we also derive conditions for our result to hold in the presence of vertical reciprocity.
Keywords: D03; D83; J33; 330; extra effort; horizontal reciprocity; negative reciprocity; Vergütungssystem; Extensives Spiel; Austauschtheorie (Soziologie); Information; Theorie